STRENGTHENING THE ROLE OF THE CONSTITUTIONAL COURT BY RESPECTING THE UNCONSTITUTIONALITY DECISIONS - Elena ANGHEL (Challenges of the Knowledge Society)
As a result of the revision of the Constitution in 2003, art. 147 of the Basic Law strengthened the binding legal effect of decisions declaring the unconstitutionality of laws and ordinances, an aspect that was required to strengthen the role of the Constitutional Court. Thus, according to art. 147 para. (4) of the Constitution, the decisions of the Constitutional Court are published in the Official Gazette of Romania. From the date of publication, decisions are generally binding and have force only for the future. From the moment the decisions of the Constitutional Court are published in the Official Gazette of Romania, the legal norms declared as unconstitutional cease to have legal effects for the future. As the Constitutional Court ruled, regarding the general binding effect of its decisions, jurisprudence must be taken into account by all authorities involved in the process of applying laws and Government ordinances. The constitutional consecration of the general binding character of the decisions of the Constitutional Court determines that they are imposed on all legal subjects, just like a normative act, unlike the decisions of the courts, which produce effects inter partes litigantes. But, as I will highlight in this study, the effectiveness of unconstitutionality decisions depends on the behavior of public authorities after the moment Constitutional Court states a non-compliance with the provisions of the Basic Law.